Development of a Solvent Extraction Process for the Recovery of Nickel and Cobalt from Nitrate Solutions - Ichlas, Zela Tanlega (Curtin University, 2015)
A direct solvent extraction (DSX) process consisting of two sequential solvent extraction circuits but using only one extractant—bis(2,4,4 trimethylpethyl)phosphinic acid (Cyanex® 272)—for separating aluminium along with zinc, cobalt along with manganese, and nickel along with the soluble impurities magnesium and calcium from nitrate media simulating nitric acid leach solutions was conceived and experimentally evaluated. A proof-of-concept that the process is effective in treating nitric acid leach solutions of laterite nickel ores was achieved.